Mathematical modeling of frozen rock massifs temperature fields considering phase transitions during the shaft deepening - Suleimanov, R.N.; Chekalkin, A.A. (Perm Federal Research Centre Journal, 2020)
The object of the research is the formation of frozen rock massif during the shaft deepening. The purpose of the work is to create a mathematical model of the rock mass dimensional temperature fields in the process of freezing wells during the mine shaft penetration. This work was carried out at the Perm National Research Polytechnic University. Design calculations provided by the customer, analytical solution of the unsteady heat conduction equation to determine the preliminary calculation of time of the frozen rock massif formation were done. ANSYS application package was used to simulate the dynamics of the temperature field in this work, with which it is also possible to determine the ice formation time in the rock massif. The initial geometrical and thermophysical information was prepared in the geographic information system «ArcGIS». Dependences frozen rock massif thickness on time and the initial temperature of the environment are obtained. The approximate dates for the formation the required thickness of the frozen rock massif, which are required for the shaft deepening, are determined.